Chiang mai digital craft: A case study of craftsmanship’s knowledge representation using digital content technology - Suepphong Charnbumroong (2018)
© Springer International Publishing AG 2017. Chiang Mai is known as the capital city of handicraft and tourism industry of Thailand. It generates source of income and employment to the local people for a long time. Nowadays, the craftsmen have tried to exploited their wisdom, creativity, skills and technology to enhance the product’s value in order to create the sustainable and higher economic growth. However, most of the time, the created value was not delivered along with the product or transferred via seller. Therefore, buyer could not perceive the wisdom, creativity, or craftsmanship skill of the purchased product. Our work aimed at applying the notion of digital content e.g. storytelling, 360-degree images, 3D-model, or augmented reality to preserve the added value and deliver to the customer. Then, the digital content was conveyed to customer through various IT tools i.e. website, web application, video streaming, and mobile application.